Strategi Efektif dalam Manajemen Kelas untuk Meningkatkan Keterlibatan Siswa - Rahayu, Sri; Sudharsono, Muhamad; Damayanti, Sherli; Rahmah, Laila (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Increasing student participation is one of the main goals in education.Effective classroom management plays a key role in achieving this goal. This overview describes some effective classroom management strategies to increase student participation. Create a positive and informative learning environment. This can be achieved by building positive relationships with students, setting clear rules and expectations, and positively reinforcing desired behaviors. Implement active learning that is student-centered.This can be done by using various learning methods, such as collaborative learning, project-based learning and problem-based learning. Provide effective feedback and evaluation. Effective feedback and assessment help students understand their progress and learn from their mistakes. Parent and community involvement. Parents and the community can play an important role in supporting student learning.